SISTEM PELAYANAN DAN MANFAAT BADAN PENYELENGGARA JAMINAN SOSIAL (BPJS) KESEHATAN DI KELURAHAN KULIM KECAMATAN KULIM KOTA PEKANBARU - Firdaus , Muhammad; Monicha, Cindy; Padilla, Raihan safa; Annisa, Aulia (LPPM Universitas Awal Bros, 2022)
The Social Security implementation agency is a legal entity to administer social security programs to ensure that all people can meet the basic needs of a decent life. Based on the Law of the Republic of Indonesia Number 24 of 2011 concerning The Social Security implementation agency , it is stated that